Vloga NATA in EU v odzivanju na civilne krize - Malešič, Marjan (Teorija in praksa, 2022)
Contemporary crises are characterised by heterogeneity, endemicity, continuity and complexity. They impact the possibility of national and international crisis management mechanisms functioning, which are themselves also in crisis and must be adapted to the new circumstances. The analysis presented in article is focused on a comparison of NATO’s Civil Emergency Planning and the EU’s Civil Protection Mechanism. The motivation for forming each was not only functional, but political as well. The factor de-motivating states’ integration into this field is their fear of losing part of their sovereignty. Countries’ cooperation through both mechanisms enables the coordinated, synergetic and successful use of available capabilities in a crisis. While the scope of NATO’s and the EU’s response to huge crises around the world is impressive, certain shortcomings are revealed when considering individual cases, especially NATO’s limited response to the migrant crisis in Europe and the EU’s hesitant response to the initial phase of the COVID-19 pandemic
Keywords: Covid-19; COVID-19 pandemic; crisis; crisis management; crisis response; Epidemije; EU’s Mechanism for Civil Protection; Evropska unija; help; Krize; krizno upravljanje in vodenje; Mehanizem EU za civilno zaščito; migrant crisis; migrantska kriza; NATO; NATO’s Civil Emergency Planning; Natovo civilno krizno načrtovanje; odziv na krizo; pomoč